Determining the Type 2 Diabetes Risks and Healthy Lifestyle Behaviors of First Year University Students - Eroglu, Nermin; Temiz, Gamze (Dokuz Eylul Univ inst Health Sciences, 2022)
Introduction: The present study was planned and carried out as a descriptive and cross-sectional study for determining the Type 2 diabetes risks and healthy lifestyle behaviors of first year university students. Material and Methods: The study was carried with 185 students at a foundation university in Istanbul during the dates of November-December 2019. The data were acquired online via Student Information Form, Type 2 Diabetes Questionnaire (FINDRISK) and Healthy Lifestyle Behaviors Scale. Results: The mean age of the students in the study was 19.79 +/- 2.47 years, 53.5 % (n=99) were male, 29.7 % (n=55 previously graduated from another university, 62.1 % (n=115) were students and it was determined that 50.3 % (n=93) had diabetic relatives. It was observed when the diabetes risk status was examined for all participants that they are in the low risk group due to a FINDRISK total score of <7. Conclusion: The study results emphasize the importance of determining the risk for university students to be diabetic in the next decade, putting forth the individuals with high risk and moving onto the next stage for diagnosis. In addition, it has been determined that the level of knowledge of students may have a positive impact on their healthy lifestyle behaviors.
Eroglu, Nermin/0000-0003-4780-3049
Keywords: Type 2 Diabetes; Diabetes Risk; Healthy Lifestyle; University Student; Beslenme Ve Diyetetik; Endokrinoloji Ve Metabolizma; Sağlık Politikaları Ve Hizmetleri